ΕDECES MODEL: Learning Design For Technology Enhanced Learning - Themelis, Chryssa (Proceedings of the International Conference on Networked Learning, 2016)
The workshop aims to address trends in learning, education, job market and EU priorities which could lead to different instructional perspective. The format of the learning design is based on a new model called EDECES: create more experiences (less instructions more real - life scenarios, prosopognosia, and visual representation of knowledge) and personal learning spaces (personalized curriculum, choices, mind maps), active critical dialogue and peer reviewing, explanations more about how participants have learnt rather than what, and adaptation to new digital environments (non-textual reflections and real-time reflexivity), creativity (products of rhizomatic learning), constant democratic evaluation (weekly polls) and finally sharing with the community of practice (build a networked learning organism). While connecting human to human and information, the EDECES model relies on the powers of the networks to maximize impacts and reach learning objectives. It is important to discover new paths and follow them to see where they are going like Odysseus looking for Ithaca.